Penguatan Brand Desa Wisata Halal melalui Promosi Digital di Desa Perlang, Kabupaten Bangka Tengah - Cipta, Hendra; Zakirman, Al Fakhri; Musa, Musa; Ulfa, Khoirina; Rohanah, Siti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: Perlang Village, located in Central Bangka Regency, is recognized as one of the earliest halal tourism villages in Indonesia; however, it has experienced a decline in brand strength due to limited digital literacy, simple promotional strategies, and the community’s insufficient understanding of comprehensive halal tourism concepts. This Community Service Program (PKM) aims to strengthen Perlang Village's branding as a halal tourism destination by enhancing community capacity in digital marketing, promotional content development, and the use of digital marketing tools. The method applied is the Asset-Based Community Development (ABCD) approach, which emphasizes the strengthening of local assets and active community involvement. Method: supported by in-depth interviews and Focus Group Discussions (FGDs) to map the village's potential and needs. The program was conducted through a series of training activities, including the introduction to halal tourism concepts, tourism package development, digital marketing practices, and a final evaluation. Results: Increase in participants’ understanding of digital marketing strategies, their ability to produce informative promotional content, and their skills in using digital tools to expand the reach of halal tourism. Although a slight decline was observed in certain post-test indicators, this reflects participants' improved reflective awareness of higher competency standards. Overall, the program generated a positive impact in revitalizing the image of Perlang Village as a competitive halal tourism destination. Conclusion: Moving forward, continued assistance and periodic monitoring are required to ensure that Perlang Village’s branding remains strong and sustainable in attracting tourists.